Sexual selection and the evolution of condition-dependence: an experimental test at two resource levels. (17th January 2023) - Bath, Eleanor; Rostant, Wayne; Ostridge, Harrison J; Smith, Sophie; Mason, Janet S; Rafaluk-Mohr, Timm; Mank, Judith E; Chapman, Tracey; Perry, Jennifer C
Abstract: Stronger condition-dependence in sexually selected traits is well-documented, but how this relationship is established remains unknown. Moreover, resource availability can shape responses to sexual selection, but resource effects on the relationship between sexual selection and condition-dependence are also unknown. In this study, we directly test the hypotheses that sexual selection drives the evolution of stronger-condition-dependence and that resource availability affects the outcome, by evolving fruit flies ( Drosophila melanogaster ) under relatively strong or weak sexual selection (through varied sex ratios) and at resource-poor or resource-rich adult diets. We then experimentally manipulated condition via developmental diet and assessed condition-dependence in adult morphology, behavior, and reproduction. We observed stronger condition-dependence in female size in male-biased populations and in female ovariole production in resource-limited populations. However, we found no evidence that male condition-dependence increased in response to sexual selection, or that responses depended on resource levels. These results offer no support for the hypotheses that sexual selection increases male condition-dependence or that sexual selection's influence on condition-dependence is influenced by resource availability. Our study is, to our knowledge, the first experimental test of these hypotheses. If the results we report are general, then sexual selection's influence on the evolution of condition-dependence may be less important than predicted.